The microbiome-product colibactin hits unique cellular targets mediating host–microbe interaction - Mousa, Walaa K. (Frontiers in Pharmacology, 2022)
The human microbiome secreted chemistry is evolved to interact with diverse cellular machinery of both host and microbes mediating human health and diseases. One of the most puzzling, microbiome molecules is colibactin, a genotoxin encoded in some commensal and extraintestinal gut microbes and is implicated in initiating colorectal cancer. Colibactin cluster has been discovered more than 15 years ago and most of the research was focused on revealing the biosynthesis and precise structure of the cryptic encoded molecule(s) and the mechanism of carcinogenesis. In 2022, the Balskus group revealed that colibactin does not only hit targets in the eukaryotic cell machinery but also in the prokaryotic cell. To that end, colibactin crosslinks the DNA resulting in activation of the SOS signaling pathway leading to prophage induction from bacterial lysogens and modulation of virulence genes in pathogenic species. These unique activities of colibactin highlight its ecological role in shaping gut microbial communities and further consequences that impact human health. This review dives in-depth into the molecular mechanisms underpinning colibactin cellular targets in eukaryotic and prokaryotic cells aiming to understand the fine details of the role of secreted microbiome chemistry in mediating host-microbe and microbe-microbe interactions. This understanding translates into a better realization of microbiome potential and how this could be advanced to future microbiome-based therapeutics or diagnostic biomarkers.